Computational Investigation of Soil Liquefaction Susceptibility based on Standard Penetration Test Value of Miri District (Sarawak, Malaysia) - Raudhah Ahmadi, Imtiyaz Akbar Najar, Ahmad Faysal Abdullahi, Norazzlina M. Sa’don, Hasmida Hamza, Nadeem Akbar Najar (International Journal of Advanced Science and Technology, 2020)
Miri is a district of Sarawak state of Malaysia and is a coastal area located at the boundary of Brunei. This paper deciphers the analysis of liquefaction susceptibility of the Miri district. Standard penetration test with N values (SPT-N) empirical criteria has been used for evaluating the liquefaction susceptibility in the Miri district. The software LiquefyPro and LiqIT have been used for the analysis by using the Idriss and Boulanger approach as this methodology encompass a simple technique and calculation. This exploration utilized a seismic tremor record from another area well-matched from target response spectrum with comparative qualities of Sarawak earthquake acquired from the Pacific Earthquake Engineering Research Center (PEER) online database (PEER NGA) with a moment magnitude of 6.0 and peak ground acceleration as 0.15 g on the ground surface. The ground motions assigned for assessment are predominantly attentive on a good complete match for the target response spectrum and on actual earthquakes that might happen in Sarawak. Liquefaction potential index (LPI), the factor of safety (Fs) and the probability of liquefaction (PL) for each soil layer was determined and then summed up for each borehole and were used to plot the contour maps by utilizing the geographical information system (GIS). From the results, the overall area of Miri is not liquefiable, only a few sites have liquefaction index as high, moreover, the obtained results of this study by using the methodology of Idriss and Boulanger are reliable. The results of this study can be used in seismic microzonation.